Pynchon's Against the day : a corrupted pilgrim's guide - Severs, Jeffrey, 1974-; Leise, Christopher, 1978- (University of Delaware Press ; Co-published with the Rowman & Littlefield Pub. Group, 2011)
Thomas Pynchon's longest novel to date, Against the Day (2006), excited diverse but energetic opinions when it appeared on bookstore shelves nine years after the critically acclaimed Mason & Dixon. Its wide-ranging plot covers more than a decade -- from the 1893 World's Fair to the years just after World War I -- and follows hundreds of characters within its 1085 pages. Pynchon's Against the Day: A Corrupted Pilgrim's Guide offers eleven essays by established luminaries and emerging voices in the field of Pynchon criticism, each addressing a significant aspect of the novel's manifold concerns.